Polyimide resin, polyimide composition, cured film of polyimide composition and manufacturing method thereof, insulating film, protective film, and electronic component

JP7643165B2Active Publication Date: 2025-03-11DAI NIPPON PRINTING CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021079101
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-07
Publication Date
2025-03-11
Estimated Expiration
2041-05-07

AI Technical Summary

Benefits of technology

【0025】 本発明によれば、低誘電率、低誘電正接、高弾性率、及び低線熱膨張係数を備えた硬化膜を形成可能でありながら、塗膜の再溶解性の速度が速いポリイミド樹脂、当該ポリイミド樹脂を含むポリイミド組成物、ポリイミド組成物の硬化膜及びその製造方法、並びに、前記ポリイミド組成物の硬化膜を用いた絶縁膜及び保護膜、これらを含む電子部品を提供することができる。 また、本発明によれば、低誘電率、低誘電正接、高弾性率、低線熱膨張係数、及び優れた密着性を備えた硬化膜を形成可能でありながら、塗膜の再溶解性の速度が速いポリイミド組成物、ポリイミド組成物の硬化膜及びその製造方法、並びに、前記ポリイミド組成物の硬化膜を用いた絶縁膜及び保護膜、これらを含む電子部品を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643165000018
    Figure 0007643165000018
  • Figure 0007643165000001
    Figure 0007643165000001
  • Figure 0007643165000002
    Figure 0007643165000002
Patent Text Reader

Abstract

To provide a polyimide resin capable of producing a cured film having a low dielectric constant, a low dielectric loss tangent, a high elastic modulus and a low linear thermal expansion coefficient, while having a lower speed in remelting properties of a coating film, and also to provide a polyimide composition including the polyimide resin, a cured film of the polyimide composition and a manufacturing method thereof, an insulator film and a protective film using the cured film of the polyimide composition, and an electronic component including these.SOLUTION: A polyimide resin is obtained by polymerizing: (1) 2,2'-bis(trifluoromethyl) benzidine; (2) 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride; (3) pyromellitic acid anhydride; and (4) a compound below.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyimide resin, a polyimide composition, a cured film of a polyimide composition and a method for producing the same, an insulating film, a protective film, and an electronic component. [Background technology]

[0002] In recent years, electronic devices have rapidly become smaller, thinner, and lighter, and semiconductor devices are also becoming more highly integrated and smaller. Development of semiconductor devices that can accommodate this miniaturization and high integration has progressed, including wafer-level packaging (WLP), 2.5-dimensional integrated circuits (2.5D ICs) that use interposers, and three-dimensional integrated circuits (3D ICs) that are made by thinning wafers and stacking the resulting dies and connecting them with through-silicon vias (TSVs).

[0003] Polyimide resins, which have excellent heat resistance, electrical insulation, and mechanical properties, have been used in the past for insulating materials in electronic components, passivation films in semiconductor devices, surface protective films, interlayer insulating films, etc. Polyimide resins are resins obtained by dehydrating and ring-closing polyamic acids obtained by condensation reactions of tetracarboxylic dianhydrides and diamines. However, conventional polyimides have the disadvantages of high curing temperature and large post-cure shrinkage. Large post-cure shrinkage leads to large residual stress in the cured polyimide film, which causes bending of semiconductor substrates such as silicon wafers. For example, in the next generation of chip configurations used in 3D integrated circuits, silicon wafers need to be thinned to 20 μm or so in cutting-edge applications to meet the requirements for vertical integration. These thin wafers are extremely brittle, and excessive residual stress in the packaging materials used can be very detrimental. Therefore, low curing temperature and small post-cure shrinkage are important requirements for packaging materials required for new semiconductor packaging technologies such as advanced wafer-level packaging.

[0004] Patent Document 1 discloses a polyimide using a diamine having an indane skeleton as a polyimide that satisfies the requirements for a packaging material necessary for a new semiconductor packaging technology, such as low-temperature curing property, a low linear thermal expansion coefficient, and solubility in environmentally and semiconductor-friendly solvents.

[0005] On the other hand, Patent Document 2 describes a polyimide obtained by reacting a tetracarboxylic dianhydride obtained by reacting trimellitic anhydride chloride with 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol with 2,2'-bis(trifluoromethyl)benzidine, and a cured film of a polyimide composition using the polyimide. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 6467433 [Patent Document 2] Patent No. 6165153 Summary of the Invention [Problem to be solved by the invention]

[0007] The polyimide in Patent Document 1 is described as a polyimide that satisfies the requirements of low-temperature curing property, low linear thermal expansion coefficient, solubility in environmentally and semiconductor-friendly solvents, etc. However, the linear thermal expansion coefficient of the polyimide in Patent Document 1 is 46 ppm / ° C. or 47 ppm / ° C., which is still significantly different from the linear thermal expansion coefficient of the semiconductor substrate, and therefore polyimides with a lower linear thermal expansion coefficient are desired. Furthermore, the packaging materials required for new semiconductor packaging technologies must have low-temperature curing properties, a low linear thermal expansion coefficient, and solvent solubility, as well as low dielectric properties (low relative dielectric constant, low dielectric tangent) to reduce power consumption and a high elastic modulus to ensure the strength of the redistribution layer.

[0008] The polyimide of Patent Document 2 is described as having excellent transparency, high heat resistance, and low linear thermal expansion coefficient, and exhibiting solvent processability (excellent solubility and film-forming ability) in a low hygroscopic solvent, with the aim of obtaining a substrate to replace a glass substrate. However, the polyimide described in Patent Document 2 has a problem that the re-dissolving rate of the coating film (dried film) is slow, as shown in the comparative example described later. In the manufacturing process, a polyimide composition that has been dried once and whose solid content is easily dissolved again in a cleaning solvent is required to have a high re-dissolving rate. Generally, if the molecular weight of the polyimide is reduced, the re-dissolving rate of the coating film increases, but in that case, the mechanical properties (elastic modulus) decrease, and there is a trade-off between the re-dissolving rate of the coating film and the elastic modulus.

[0009] The present invention has been made in consideration of the above problems, and has an object to provide a polyimide resin capable of forming a cured film having a low dielectric constant, a low dielectric tangent, a high elastic modulus, and a low coefficient of linear thermal expansion while exhibiting a high re-dissolving rate of the coating film; a polyimide composition containing the polyimide resin; a cured film of the polyimide composition and a method for producing the same; and an insulating film and a protective film using a cured film of the polyimide composition, and electronic devices containing them. [Means for solving the problem]

[0010] The present invention provides a polyimide resin comprising structural units represented by the following formula (1) in an amount of 40 mol % or more and less than 70 mol % of all structural units, and structural units represented by the following formula (2) in an amount of more than 10 mol % and not more than 60 mol % of all structural units.

[0011] [ka]

[0012] The polyimide resin according to the present invention may have a weight average molecular weight of 150,000 or more as calculated using polystyrene standards by gel permeation chromatography, in order to be a polyimide resin capable of forming a cured film having a low dielectric constant, a low dielectric tangent, a high elastic modulus, and a low coefficient of linear thermal expansion, while having a high re-dissolving rate of the coating film.

[0013] The polyimide resin according to the present invention may further contain 20 mol % or less of a structural unit represented by the following formula (3) based on all structural units, in order to obtain a polyimide resin capable of forming a cured film having a low dielectric constant, a low dielectric tangent, a high elastic modulus, and a low coefficient of linear thermal expansion while having a high re-dissolving rate of the coating film.

[0014] [ka]

[0015] The present invention also provides a polyimide composition comprising the polyimide resin according to the present invention and an organic solvent.

[0016] Furthermore, as one of the preferred embodiments of the polyimide composition, the present invention provides a polyimide composition containing the polyimide resin according to the present invention, an epoxy compound having three or more epoxy groups in one molecule and having a glycidyl amine moiety, and an organic solvent, from the viewpoint of the ability to form a cured film having excellent adhesion (hereinafter, the polyimide composition containing the epoxy compound may be referred to as the "polyimide composition of embodiment A").

[0017] The polyimide composition of embodiment A according to the present invention may further contain a compound represented by the following general formula (A) in order to improve adhesion.

[0018] [ka] (In formula (A), R arepresents a monovalent group containing at least one selected from the group consisting of a glycidyl group, a (meth)acryloyl group, an acid anhydride group, a hydroxy group, a triazine group, and an amino group; R b and R c are each independently an alkyl group having 1 to 5 carbon atoms, n is an integer of 1 to 10, and m is an integer of 1 to 3.

[0019] The present invention also provides a method for producing a polyimide film by applying the polyimide composition according to the present invention onto a substrate and drying the applied polyimide composition to form a coating film; The present invention also provides a method for producing a cured film of a polyimide composition, the method comprising the step of heating the coating film to form a cured film.

[0020] In the method for producing a cured film of a polyimide composition according to the present invention, the temperature at which the coating film is heated may be 150° C. or higher and 240° C. or lower.

[0021] The present invention also provides a cured film of a polyimide composition obtained by curing the polyimide composition according to the present invention.

[0022] A cured film of the polyimide composition may have a dielectric constant of 3.60 or less and a dielectric loss tangent of 0.020 or less, as measured at 10 GHz using a split cylinder resonator. Furthermore, the cured film of the polyimide composition may have a linear thermal expansion coefficient at 100°C to 150°C of 30 ppm / °C or less. Furthermore, a cured film of the polyimide composition may have a tensile modulus at 25° C. of 4.5 GPa or more.

[0023] The present invention also provides a cured film of the polyimide composition according to embodiment A of the present invention, wherein the adhesion to a silicon nitride substrate is such that the number of unpeeled cross-cuts in a cross-cut test according to JIS K 5400-8.5 is 80% or more of the total.

[0024] The present invention provides an insulating film prepared using a cured film of the polyimide composition according to the present invention. The present invention also provides a protective film prepared using a cured film of the polyimide composition according to the present invention. The present invention also provides an electronic component including the insulating film according to the present invention or the protective film according to the present invention. Effect of the Invention

[0025] ADVANTAGEOUS EFFECTS OF THE PRESENT DISCLOSURE According to the present invention, there are provided a polyimide resin capable of forming a cured film having a low dielectric constant, a low dielectric tangent, a high elastic modulus, and a low coefficient of linear thermal expansion while exhibiting a high re-dissolving rate of a coating film; a polyimide composition containing the polyimide resin; a cured film of the polyimide composition and a method for producing the same; and an insulating film and a protective film using a cured film of the polyimide composition, and electronic devices including these. Furthermore, according to the present invention, it is possible to provide a polyimide composition capable of forming a cured film having a low dielectric constant, a low dielectric dissipation factor, a high elastic modulus, a low coefficient of linear thermal expansion, and excellent adhesion, while the coating film has a fast re-dissolving rate, a cured film of the polyimide composition and a method for producing the same, an insulating film and a protective film using the cured film of the polyimide composition, and electronic devices including these. [Brief description of the drawings]

[0026] [Figure 1] FIG. 1 is a manufacturing process diagram of a semiconductor device having a multilayer wiring structure, which is an electronic component according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] The polyimide resin, polyimide composition, cured film of the polyimide composition and its production method, insulating film, protective film, and electronic component according to the present invention will be described in detail below. In addition, terms used in this specification that specify shapes, geometric conditions, and the degree thereof, such as "parallel," "orthogonal," and "same," as well as values ​​of length and angle, are not to be bound by strict meanings, but are to be interpreted to include a range within which similar functions can be expected. In the drawings attached to this specification, the scale and aspect ratios may be appropriately changed and exaggerated from those of the actual objects for the convenience of illustration and ease of understanding. In this specification, (meth)acrylic means each of acrylic and methacrylic, and (meth)acryloyl means each of acryloyl and methacryloyl. In addition, in this specification, the use of "to" indicating a numerical range is used to mean that the numerical values ​​before and after it are included as the lower limit and upper limit.

[0028] I. Polyimide resin A polyimide resin according to one embodiment of the present invention is a polyimide resin that contains structural units represented by the following formula (1) in an amount of 40 mol % or more and less than 70 mol % of all structural units, and structural units represented by the following formula (2) in an amount of more than 10 mol % and not more than 60 mol % of all structural units.

[0029] [ka]

[0030] The polyimide resin according to one embodiment of the present invention is capable of forming a cured film having a low dielectric constant, a low dielectric tangent, a high elastic modulus, and a low coefficient of linear thermal expansion, while the coating film has a high re-dissolving rate. The structural unit of the present invention of formula (1) contains a tetracarboxylic acid residue of a specific structure containing a parabiphenylene group with a twisted dihedral angle via an ester bond in the main chain, and a diamine residue of a specific structure containing a parabiphenylene group with a twisted dihedral angle due to a trifluoromethyl group. Since the structural unit contains two parabiphenylene groups with twisted dihedral angles, the main chain structure is linear and rigid, so that a polyimide resin containing a large number of structural units of formula (1) has a slow re-dissolving rate of a coating film even if it has solvent solubility. In contrast, in the polyimide resin of the present invention, a specific amount of the structural unit of the formula (1) is combined with a specific amount of the structural unit of the formula (2). The structural unit of the formula (2) has a 3,3',4,4'-benzophenonetetracarboxylic dianhydride residue, and therefore can have a structure in which the main chain is greatly bent. Therefore, it is presumed that combining a specific amount of the structural unit of the formula (1) with a specific amount of the structural unit of the formula (2) has the effect of moderately weakening the intermolecular forces in the polyimide resin, and that the re-dissolving speed of the coating film is increased even in a high molecular weight that can achieve a high elastic modulus. In addition, since the bending direction of the 3,3',4,4'-benzophenonetetracarboxylic dianhydride residue is fixed by the carbonyl group, unlike the case where it is linked by a hexafluoropropane group, it is presumed that the mechanical properties of the polyimide resin are unlikely to be reduced, and can be maintained or even improved. In addition, since the linear and rigid main chain structure contains many para-biphenylene groups with twisted dihedral angles as structural units and also contains an appropriate amount of bending components, it is believed that it is possible to form a cured film with low dielectric constant, low dielectric tangent, high elastic modulus, and low linear thermal expansion coefficient. The polyimide resin of the present invention has a high resolubility rate of the coating film, which improves the cleaning efficiency of the coating device during the manufacturing process, thereby contributing to improving the cleaning efficiency and work efficiency. In addition, it is possible to select a relatively safe cleaning solvent, which also contributes to reducing the burden on the workers. Furthermore, the polyimide resin of the present invention is a soluble polyimide resin and has a low curing temperature, and a curing temperature of 150° C. or higher and 240° C. or lower can be adopted.

[0031] The polyimide resin according to one embodiment of the present invention will be described in detail below. The tetracarboxylic acid residue refers to a residue obtained by removing four carboxyl groups from a tetracarboxylic acid, and represents the same structure as a residue obtained by removing an acid dianhydride structure from a tetracarboxylic acid dianhydride, and may be a tetracarboxylic acid dianhydride residue. Moreover, the diamine residue refers to a residue obtained by removing two amino groups from a diamine.

[0032] In the polyimide resin according to one embodiment of the present invention, the constitutional unit represented by the formula (1) can be obtained by reacting a tetracarboxylic dianhydride represented by the following formula (1-1) with 2,2'-bis(trifluoromethyl)benzidine.

[0033] [ka]

[0034] In the polyimide resin according to one embodiment of the present invention, the constituent units represented by the formula (1) are 40 mol % or more and less than 70 mol % of all the constituent units in order to obtain a polyimide capable of forming a cured film having a low dielectric constant, a low dielectric loss tangent, a high elastic modulus, and a low linear thermal expansion coefficient, while having a high resolubility rate of the coating film. The constituent units represented by the formula (1) may be 45 mol % or more, 50 mol % or more, or even 55 mol % or more of all the constituent units in order to obtain a polyimide having a high resolubility rate of the coating film. On the other hand, the constituent units represented by the formula (1) may be 65 mol % or less, or even 60 mol % or less of all the constituent units in order to obtain a low linear thermal expansion coefficient.

[0035] In the polyimide resin according to one embodiment of the present invention, the constitutional unit represented by the formula (2) can be obtained by reacting 3,3',4,4'-benzophenonetetracarboxylic dianhydride with 2,2'-bis(trifluoromethyl)benzidine. In the polyimide resin according to one embodiment of the present invention, the constitutional unit represented by the formula (2) is more than 10 mol % and 60 mol % or less of all constitutional units in order to obtain a polyimide capable of forming a cured film having a low dielectric constant, a low dielectric loss tangent, a high elastic modulus, and a low linear thermal expansion coefficient, while having a high resolubility rate of the coating film. The constitutional unit represented by the formula (2) may be 15 mol % or more, 20 mol % or more, or even 30 mol % or more of all constitutional units in order to obtain a low linear thermal expansion coefficient. On the other hand, the constitutional unit represented by the formula (2) may be 55 mol % or less, 50 mol % or less, or even 45 mol % or less of all constitutional units in order to obtain a polyimide having a high resolubility rate of the coating film.

[0036] In the polyimide resin according to one embodiment of the present invention, in order to obtain a polyimide capable of forming a cured film having a low dielectric constant, a low dielectric tangent, a high elastic modulus, and a low coefficient of linear thermal expansion while having a high re-dissolving rate of the coating film, the sum of the constitutional units represented by the formula (1) and the constitutional units represented by the formula (2) may be 75 mol % or more, 80 mol % or more, or 85 mol % or more of all constitutional units.

[0037] In the polyimide resin according to one embodiment of the present invention, the specific amount of the structural unit represented by formula (1) and the structural unit represented by formula (2) is contained, and the effect of the present invention is not impaired, other polyimide structural units different from the structural unit represented by formula (1) and the structural unit represented by formula (2) may be contained. The other polyimide structural units may be 25 mol % or less, 20 mol % or less, or 15 mol % or more of the total structural units, from the viewpoint of forming a cured film having a low dielectric constant, a low dielectric loss tangent, a high elastic modulus, and a low coefficient of linear thermal expansion, while providing a polyimide having a high re-dissolving rate of the coating film.

[0038] The tetracarboxylic dianhydride used as a copolymerization component in combination with the tetracarboxylic dianhydride represented by the formula (1-1) and 3,3',4,4'-benzophenonetetracarboxylic dianhydride to form another polyimide structural unit may be at least one of tetracarboxylic dianhydrides having an aromatic ring and tetracarboxylic dianhydrides having an aliphatic ring.

[0039] Examples of tetracarboxylic dianhydrides having an aromatic ring include pyromellitic dianhydride, 2,2',3,3'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 2,2',3,3'-biphenyl tetracarboxylic dianhydride, 2,3,3',4'-biphenyl tetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride, bis(3, 4-dicarboxyphenyl)sulfone dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 1,3-bis[(3,4-dicarboxy)benzoyl]benzene dianhydride, 1,4-bis[(3,4-dicarboxy)benzoyl]benzene dianhydride, 2,2-bis{4-[4-(1,2-dicarboxy)phenoxy]phenyl}propane dianhydride, 2,2-bis{4-[3-(1,2-dicarboxy)phenoxy]phenyl}propane dianhydride, bis{4-[4-(1,2-dicarboxy)phenoxy]phenyl}ketone dianhydride, bis{4-[3-(1,2-dicarboxy)phenoxy]phenyl}ketone dianhydride, 4,4'-bis[4-(1,2-dicarboxy)phenoxy]biphenyl dianhydride, 4,4'-bis[3-(1,2-dicarboxy)phenoxy]biphenyl dianhydride, bis{4-[4-(1,2-dicarboxy)phenoxy]phenyl}ketone dianhydride, bis{4-[3-(1,2-dicarboxy)phenoxy]phenyl}ketone dianhydride, bis{4-[4 -(1,2-dicarboxy)phenoxy]phenyl}sulfone dianhydride, bis{4-[3-(1,2-dicarboxy)phenoxy]phenyl}sulfone dianhydride, bis{4-[4-(1,2-dicarboxy)phenoxy]phenyl}sulfide dianhydride, bis{4-[3-(1,2-dicarboxy)phenoxy]phenyl}sulfide dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 3,4'-(hexafluoroisopropylidene)diphthalic anhydride, 3,3'-(hexafluoroisopropylidene)diphthalic anhydride, 4,Examples of the dianhydride include 4'-oxydiphthalic anhydride, 3,4'-oxydiphthalic anhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,2,3,4-benzenetetracarboxylic dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, 2,3,6,7-anthracenetetracarboxylic dianhydride, and 1,2,7,8-phenanthrenetetracarboxylic dianhydride. Examples of tetracarboxylic dianhydrides having an aliphatic ring include cyclohexanetetracarboxylic dianhydride, cyclopentanetetracarboxylic dianhydride, dicyclohexane-3,4,3',4'-tetracarboxylic dianhydride, cyclobutanetetracarboxylic dianhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, and 1,1'-bicyclohexane-3,3',4,4'-tetracarboxylic dianhydride. These may be used alone or in combination of two or more.

[0040] As the tetracarboxylic dianhydride used as a copolymerization component for forming other polyimide structural units, at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, and cyclobutanetetracarboxylic dianhydride is preferably used in terms of excellent mechanical properties of the polyimide resin, and pyromellitic dianhydride is preferably used in terms of improved elastic modulus and low linear thermal expansion coefficient.

[0041] In addition, examples of diamines that are used as copolymerization components in combination with 2,2'-bis(trifluoromethyl)benzidine to form other polyimide structural units include at least one diamine having an aromatic ring and a diamine having an aliphatic ring. Examples of diamines having an aromatic ring include p-phenylenediamine, m-phenylenediamine, 2,4-diaminotoluene, 2,5-diaminotoluene, 2,4-diaminoxylene, 2,4-diaminodurene, 4,4'-diaminodiphenylmethane, 4,4'-methylenebis(2-methylaniline), 4,4'-methylenebis(2-ethylaniline), 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-methylenebis(2,6-diethylaniline), 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 2,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminobenzophenone, and 3,3'-diaminobenzophenone. , 4,4'-diaminobenzanilide, 4-aminophenyl-4'-aminobenzoate, benzidine, 3,3'-dihydroxybenzidine, 3,3'-dimethoxybenzidine, o-tolidine, m-tolidine, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(3-aminophenoxy)phenyl)sulfone, bis(4-(4-aminophenoxy)phenyl)sulfone, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)hexafluoropropane, 2,2-bis(4-aminophenyl)hexafluoropropane, p-terphenylenediamine, and the like. Examples of diamines having an aliphatic ring include 4,4'-methylenebis(cyclohexylamine), isophoronediamine, trans-1,4-diaminocyclohexane, cis-1,4-diaminocyclohexane, 1,4-cyclohexanebis(methylamine), 2,5-bis(aminomethyl)bicyclo[2.2.1]heptane, 2,6-bis(aminomethyl)bicyclo[2.2.1]heptane, 3,8-bis(aminomethyl)tricyclo[5.2.1.0]decane, 1,3-diaminoadamantane, 2,2-bis(4-aminocyclohexyl)propane, and 2,2-bis(4-aminocyclohexyl)hexafluoropropane. These may be used alone or in combination of two or more.

[0042] The diamine used as a copolymerization component to form another polyimide structural unit may be at least one of p-phenylenediamine, m-phenylenediamine, 2,4-diaminotoluene, 2,5-diaminotoluene, 2,4-diaminoxylene, 2,4-diaminodurene, benzidine, 3,3'-dihydroxybenzidine, 3,3'-dimethoxybenzidine, o-tolidine, m-tolidine, and p-terphenylenediamine, from the viewpoint of excellent mechanical properties of the polyimide.

[0043] The polyimide resin of the present invention preferably further contains a structural unit represented by the following formula (3) in an amount of 20 mol % or less of all structural units, from the viewpoints of improving the elastic modulus and reducing the linear thermal expansion coefficient. When the structural unit represented by the following formula (3) is contained, the structural unit represented by the following formula (3) may account for 3 mol % or more of all structural units, or may account for 5 mol % or more, or may account for 17 mol % or less of all structural units.

[0044] [ka]

[0045] The constitutional unit represented by the above formula (3) can be obtained by reacting pyromellitic dianhydride with 2,2-bis(trifluoromethyl)-4,4-diaminobiphenyl.

[0046] In addition, in the polyimide resin of the present invention, the sum of the constitutional units represented by the formula (1), the constitutional units represented by the formula (2), and the constitutional units represented by the formula (3) may be 90 mol % or more, 95 mol % or more, 98 mol % or more, or even 100 mol % of all constitutional units of the polyimide resin.

[0047] Furthermore, the polyimide resin according to one embodiment of the present invention may partially have a structure different from the polyimide constitutional unit as long as the effect of the present invention is not impaired. In the polyimide resin of the present invention, the sum of the polyimide constituent units may be 90 mol % or more, 95 mol % or more, 98 mol % or more, or 100 mol % of all constituent units of the polyimide resin. Examples of structures different from the polyimide constituent unit include a constituent unit in which a tetracarboxylic acid component is not completely imidized and has a polyamic acid structure in part, a polyamideimide constituent unit containing a tricarboxylic acid residue such as trimellitic anhydride, and a polyamide constituent unit.

[0048] The content (mol %) of each residue in the polyimide resin of the present invention can be determined by confirming the ratio of the raw material composition, for example, by the following method. First, a sodium hydroxide solution is prepared by mixing 2.0 g of sodium hydroxide, 25 mL of water, and 25 mL of methanol, and 200 mg of polyimide resin is dissolved in 10 mL of the sodium hydroxide solution. The solution is heated in a pressure-resistant container at 250 °C for 1 hour to promote depolymerization of the polyimide resin. The resulting solution is extracted with chloroform and water, and the decomposition product (raw material monomer) is separated. The ratio of the raw material composition is measured by gas chromatography (HP6890 / HP5973 manufactured by Agilent Technologies) (the column is "InertCap 5MS / Sil (30 m x 250 μm x 0.25 μm, manufactured by GL Sciences)" and the measurement conditions are 50 °C for 5 min, then heated to 320 °C at 10 °C / min and held for 3 min). The composition ratio of each raw material can be calculated from the area ratio of gas chromatography. The content (mol%) of each residue in the polyimide resin can be determined from the ratio of the raw materials used during resin production. The structure of the polyimide resin can be determined using NMR, various mass spectrometry, elemental analysis, XPS / ESCA, TOF-SIMS, etc.

[0049] The method for producing the polyimide resin according to one embodiment of the present invention is not particularly limited. For example, the polyimide resin can be produced through a step of reacting two or more kinds of tetracarboxylic acid dianhydrides including the tetracarboxylic acid dianhydride represented by the formula (1-1) and 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride, and a tetracarboxylic acid dianhydride having an aromatic ring or an aliphatic ring as required, with one or more kinds of diamines including 2,2'-bis(trifluoromethyl)benzidine and a diamine having an aromatic ring or an aliphatic ring as required, to obtain a polyimide precursor (polyamic acid), and a step of imidizing the obtained polyimide precursor (polyamic acid).

[0050] The tetracarboxylic dianhydride represented by the general formula (1-1) can be obtained by a known esterification reaction using 2,2',3,3'5,5'-hexamethyl-biphenyl-4,4'-diol and trimellitic acids. Examples of the trimellitic acids include trimellitic anhydride and trimellitic anhydride halide. For the synthesis method of the tetracarboxylic dianhydride represented by the general formula (1-1), refer to Japanese Patent No. 6165153 as appropriate. The tetracarboxylic dianhydride having an aromatic ring or an aliphatic ring and the diamine having an aromatic ring or an aliphatic ring, which are used as necessary, may be appropriately selected from the above-mentioned tetracarboxylic dianhydride and the above-mentioned diamine, respectively. The method for producing the tetracarboxylic dianhydride having an aromatic ring or an aliphatic ring and the diamine having an aromatic ring or an aliphatic ring, which are used as necessary, is not particularly limited, and a known production method may be appropriately adopted, or a commercially available product may be appropriately used.

[0051] The polyimide precursor is obtained by reacting the tetracarboxylic dianhydride with the diamine in a solvent. The solvent used in the synthesis of the polyimide precursor is not particularly limited as long as it can dissolve the tetracarboxylic dianhydride and diamine, and for example, an aprotic polar solvent can be used. In the present invention, it is preferable to use an organic solvent containing a nitrogen atom such as N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, etc.; γ-butyrolactone, etc. The organic solvent is a solvent containing a carbon atom.

[0052] The polymerization reaction procedure can be appropriately selected from known methods. For example, in a low humidity environment by nitrogen substitution, first, a diamine is dissolved in a polymerization solvent in a reaction vessel, and then an acid dianhydride in an amount substantially equimolar to the diamine is gradually added to the solution, followed by stirring for 0.5 to 150 hours, preferably 1 to 48 hours, using a mechanical stirrer or the like at a temperature in the range of 0 to 100° C., preferably 20 to 60° C. In this case, the monomer concentration is usually in the range of 5 to 50% by mass, preferably 10 to 40% by mass.

[0053] The polyimide precursor solution is prepared by combining at least two kinds of tetracarboxylic dianhydrides. The polyamic acid may be synthesized by adding at least two kinds of acid dianhydrides at once to a polymerization solvent in which a diamine is dissolved, or the sequence in which each raw material is incorporated into a polymer chain may be controlled to some extent by adding at least two kinds of acid dianhydrides in a stepwise manner in an appropriate molar ratio to a reaction solution. For example, a tetracarboxylic dianhydride represented by general formula (1-1) may be added to a reaction solution in which a diamine is dissolved, and reacted to synthesize an amic acid in which the tetracarboxylic dianhydride represented by general formula (1-1) reacts with the diamine, and then 3,3',4,4'-benzophenonetetracarboxylic dianhydride and, if necessary, a tetracarboxylic dianhydride having an aromatic ring or an aliphatic ring may be added thereto, and, if necessary, a diamine may be further added to polymerize the polyamic acid. When polymerized by this method, the tetracarboxylic dianhydride represented by general formula (1-1) is introduced into the polyamic acid in a linked form via one diamine. Polymerizing polyamic acid by such a method is preferable because it allows the positional relationship of tetracarboxylic acid residues having a specific structure, which contains a para-biphenylene group with a twisted dihedral angle in the main chain via an ester bond, to be specified to a certain extent, and it is likely that the weight average molecular weight as calculated in terms of polystyrene by gel permeation chromatography will be 150,000 or more, and it is easy to obtain a cured film having excellent elastic modulus and low linear thermal expansion coefficient.

[0054] When the number of moles of diamine in the polyimide precursor solution (polyamic acid solution) is a and the number of moles of tetracarboxylic dianhydride is b, b / a may be 0.9 or more and 1.1 or less, or 0.95 or more and 1.05 or less. In terms of the resolubility of the coating film and the weight average molecular weight calculated as polystyrene by gel permeation chromatography, b / a may be 0.98 or more and 1.01 or less, or 0.99 or more and less than 1.00. By setting it in such a range, the molecular weight (degree of polymerization) of the obtained polyamic acid can be appropriately adjusted, and the functional groups at the terminals can also be adjusted.

[0055] In order to prepare a polyimide having a weight average molecular weight of 150,000 or more as calculated using polystyrene standards by gel permeation chromatography, it is preferable to carry out the reaction by gradually adding an acid dianhydride to a reaction solution in which a diamine is dissolved, while measuring by gel permeation chromatography that the molecular weight reaches a desired range, in the preparation of the polyimide precursor.

[0056] From the viewpoint of excellent mechanical properties of polyimide, the weight average molecular weight of the polyimide precursor (polyamic acid) may be 150,000 or more, 180,000 or more, or 200,000 or more. On the other hand, from the viewpoint of re-solubility of the coating film, the weight average molecular weight of the polyimide precursor (polyamic acid) may be 1,000,000 or less, 500,000 or less, or 400,000 or less. The weight average molecular weight of the polyimide precursor can be measured by gel permeation chromatography (GPC).

[0057] As the polyimide precursor (polyamic acid) used for imidization, a polyimide precursor solution obtained by a synthesis reaction may be used as it is, or the solvent of the polyimide precursor solution may be dried and the solution may be dissolved in another solvent.

[0058] Methods for imidizing a polyimide precursor include thermal imidization, which involves a dehydration ring-closing reaction by heating, and chemical imidization, which involves a dehydration ring-closing reaction using a chemical imidization agent (a dehydration ring-closing agent).Of these, chemical imidization is preferred from the viewpoint of avoiding changes in molecular weight due to depolymerization of polyamic acid caused by heating. When chemical imidization is performed, known compounds such as amines such as pyridine and β-picolinic acid, carbodiimides such as dicyclohexylcarbodiimide, and acid anhydrides such as acetic anhydride may be used as chemical imidization agents. The acid anhydride is not limited to acetic anhydride, but may include, but is not limited to, propionic anhydride, n-butyric anhydride, benzoic anhydride, trifluoroacetic anhydride, and the like. In addition, tertiary amines such as pyridine and β-picolinic acid may be used in combination. However, since these amines may adversely affect the properties if they remain in the cured film, the reaction solution in which the polyimide precursor is reacted to polyimide may be purified by reprecipitation or the like, and the chemical imidization agent components other than polyimide may be removed to 100 ppm or less of the total weight of the polyimide.

[0059] The organic solvent used in the reaction solution for chemically imidizing the polyimide precursor is not particularly limited as long as it can dissolve the polyimide precursor. For example, N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethylsulfoxide, hexamethylphosphoramide, 1,3-dimethyl-2-imidazolidinone, and other nitrogen-containing organic solvents; γ-butyrolactone, etc. can be used.

[0060] The molecular chain terminals of the polyimide may be carboxyl or amino terminals, and the terminals may be capped with a terminal capping agent. The terminal capping agent may be appropriately selected from known terminal capping agents, and examples of the terminal capping agent include monoamines, monocarboxylic acids, acid anhydrides, monoacid chloride compounds, and monoactive ester compounds. When an acid anhydride is used for chemical imidization during preparation of a polyimide, the acid anhydride may react with the amino terminal. The polyimide according to one embodiment of the present invention may have an amide bond at the terminal, or may have an acetamide group at the terminal, which is prepared by preparing a polyimide precursor having an amino terminal, and then chemically imidizing the precursor and reacting the amino terminal with an acid anhydride at the same time. In one embodiment of the present invention, the polyimide may have 10% or more of the ends of its molecular chains having amide groups, or 40% or more of the ends having amide groups, or 70% or more of the ends having amide groups, in order to improve adhesion by reacting with an additive such as an epoxy compound.

[0061] A typical method for reprecipitating the reaction solution that has been reacted to form a polyimide is to drop the reaction solution into a large amount of poor solvent while stirring it. In terms of making it easier to reduce impurities, a preferred method for reprecipitating the reaction solution is to dilute the reaction solution that has been reacted to form a polyimide to an appropriate concentration as necessary, and then gradually add a poor solvent for the polyimide to the reaction solution to precipitate the polyimide. When the poor solvent is dropped to precipitate a polyimide, the solids concentration of the reaction liquid (polyimide solution) is preferably 0.1% by mass or more and 30% by mass or less, and more preferably 1% by mass or more and 10% by mass or less, from the viewpoints of yield and efficient removal of impurities. In order to adjust the solids concentration of the polyimide solution to a level suitable for precipitation of the polyimide, the polyimide solution may be appropriately diluted with a good solvent for the polyimide. As a guideline, a good solvent for polyimide can be appropriately selected from solvents in which the solubility of polyimide at 25° C. is 20 g / 100 g or more. Moreover, the poor solvent for polyimide can be appropriately selected from solvents in which the solubility of polyimide at 25° C. is less than 20 g / 100 g, as a guideline.

[0062] For example, an organic solvent that is a good solvent for polyimide is added to the reaction solution that has been reacted to form a polyimide, and the reaction solution is diluted by stirring until it becomes uniform, and then an alcohol-based organic solvent such as t-butanol, methanol, ethanol, isopropyl alcohol, 2-butanol, cyclohexanol, or t-amyl alcohol is gradually added to precipitate the polyimide, obtaining a white slurry, which is then filtered to obtain the polyimide. The alcohol-based organic solvent may be a secondary or tertiary alcohol, among others, because it provides excellent stability to the polyimide.

[0063] The polyimide obtained by reprecipitation as described above is preferably repeatedly washed with an organic solvent to remove residual solvent. For example, the polyimide obtained by reprecipitation is washed in an organic solvent for washing, and then filtered. This washing process is repeated, and the polyimide is dried at 100° C. to 120° C. using a vacuum dryer to obtain the polyimide. The organic solvent for washing is selected from among organic solvents that are highly compatible with the residual solvent contained in the polyimide obtained by reprecipitation, are poor solvents for the polyimide, and have a boiling point lower than the drying temperature of a vacuum dryer so that they can be completely volatilized by drying at 100°C to 120°C using a vacuum dryer. For example, when the residual solvent is N,N-dimethylacetamide, N-methyl-2-pyrrolidone, etc., used in preparing the polyimide precursor, isopropyl alcohol, methanol, etc. are preferably used as the cleaning organic solvent. One or more types of cleaning organic solvents can be used.

[0064] The polyimide resin of the present invention thus obtained has a weight average molecular weight, as determined by gel permeation chromatography in terms of polystyrene, of preferably 150,000 or more as a lower limit, more preferably 180,000 or more, even more preferably 200,000 or more as an upper limit, and preferably 1,000,000 or less, more preferably 500,000 or less, even more preferably 400,000 or less. When the weight average molecular weight of the polyimide resin is equal to or more than the lower limit, it is preferable that the elastic modulus is improved and a cured film having a reduced linear thermal expansion coefficient is easily obtained, whereas when the weight average molecular weight is equal to or less than the upper limit, it is preferable that the viscosity is prevented from increasing during synthesis, composition preparation, and coating film formation, and coating film and cured film are easily formed. The weight-average molecular weight of polyimide resin can be measured by gel permeation chromatography (GPC). Specifically, polyimide resin is dissolved in N-methylpyrrolidone (NMP) at a concentration of 0.5% by mass, and the solution is filtered through a syringe filter (pore size: 0.45 μm). The developing solvent is a 10 mmol% LiBr-NMP solution, and the measurement is performed using a Tosoh GPC device (HLC-8120, column used: SHODEX GPC LF-804) with a sample injection amount of 50 μL, a solvent flow rate of 0.4 mL / min, and 37°C. The weight-average molecular weight is determined based on a polystyrene standard sample of the same concentration as the sample.

[0065] Furthermore, it is preferable that a cured film of the polyimide resin of the present invention alone has the same linear thermal expansion coefficient, dielectric constant, dielectric loss tangent, and tensile modulus as those described below for the cured film of the polyimide composition.

[0066] The polyimide resin of the present invention is a polyimide resin with a high re-dissolving rate of the coating film. For example, the polyimide resin of the present invention can be obtained by inserting a glass piece with a width of 20 mm, a length of 50 mm, and a thickness of 0.5 mm 25 mm into a 10 mass % solution (polyimide composition) of polyimide resin obtained by dissolving polyimide in cyclopentanone or N,N-dimethylacetamide with a long side vertically, and then pulling it out, and drying the polyimide composition attached to the glass surface in air at 25°C for 15 hours in a local exhaust device to prepare a coating film (air-dried film), cutting a test piece of 20 mm x 20 mm from the coating film, putting it into a glass vial containing 20 mL of cyclopentanone, and stirring it with a magnetic stirrer at 100 rpm. When the time until the coating film is completely dissolved is measured, the dissolution time can be 30 minutes or less, and further 15 minutes or less.

[0067] The polyimide resin of the present invention is capable of forming a cured film having a low dielectric constant, a low dielectric dissipation factor, a high elastic modulus, and a low coefficient of linear thermal expansion, and yet has a high re-dissolving rate when formed into a coating film. Therefore, the polyimide resin of the present invention can be suitably used in, for example, semiconductor electronic components or semiconductor devices, specifically, for applications such as a passivation film for a semiconductor, a surface protective film for a semiconductor element, an interlayer insulating film, an interlayer insulating film for multilayer wiring for high-density mounting, and an insulating film for an organic electroluminescent element. In addition to the uses described above, the polyimide resin of the present invention can also be used, for example, as members for image display devices such as liquid crystal display devices and organic EL display devices, members for touch panels, flexible printed circuit boards, members for solar cell panels such as surface protection films and substrate materials, members for optical waveguides, and other semiconductor-related members.

[0068] II. Polyimide Composition The polyimide composition of the present invention contains the polyimide resin of the present invention and an organic solvent. The polyimide composition of the present invention may further contain other components as long as the effects of the present invention are not impaired.

[0069] The polyimide resin contained in the polyimide composition of the present invention may be the same as the polyimide resin of the present invention described above, and therefore a description thereof will be omitted here. The organic solvent contained in the polyimide composition is not particularly limited as long as it is capable of dissolving the polyimide resin of the present invention described above, does not react with each component in the composition, and is capable of dissolving or dispersing these components. For example, an aprotic polar solvent or the like can be used.

[0070] Examples of the organic solvent include ester-based solvents such as γ-butyrolactone, γ-valerolactone, δ-valerolactone, γ-caprolactone, ε-caprolactone, α-methyl-γ-butyrolactone, butyl acetate, ethyl acetate, and isobutyl acetate; carbonate-based solvents such as ethylene carbonate and propylene carbonate; glycol-based solvents such as diethylene glycol dimethyl ether, triethylene glycol, and triethylene glycol dimethyl ether; phenol-based solvents such as phenol, m-cresol, p-cresol, o-cresol, 3-chlorophenol, and 4-chlorophenol; cyclopentane-based solvents such as cyclopentane, m-cresol, p-cresol, o-cresol, 3-chlorophenol, and 4-chlorophenol; Ketone solvents such as methyl ethyl ketone, diisobutyl ketone, and methyl isobutyl ketone; ether solvents such as tetrahydrofuran, 1,4-dioxane, dimethoxyethane, diethoxyethane, and dibutyl ether; and other general-purpose solvents such as acetophenone, 1,3-dimethyl-2-imidazolidinone, sulfolane, dimethyl sulfoxide, propylene glycol methyl acetate, ethyl cellosolve, butyl cellosolve, 2-methyl cellosolve acetate, ethyl cellosolve acetate, butyl cellosolve acetate, chloroform, butanol, ethanol, xylene, Examples of the solvent include toluene, chlorobenzene, turpentine, mineral spirits, and petroleum naphtha-based solvents, and two or more of these may be mixed and used. As the organic solvent contained in the polyimide composition of the present invention, it is preferable to use, among others, organic solvents containing a nitrogen atom, such as N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethylsulfoxide, hexamethylphosphoramide, and 1,3-dimethyl-2-imidazolidinone; γ-butyrolactone, cyclopentanone, and tetrahydrofuran.

[0071] In the polyimide composition of the present invention, the content of the organic solvent may be appropriately set within a range that provides a viscosity described below, for example, depending on the purpose of use and processing conditions, and is not particularly limited. The content of the organic solvent is usually preferably within a range of 70% by mass to 95% by mass, more preferably 75% by mass to 90% by mass, based on the total amount of the polyimide composition including the organic solvent.

[0072] Furthermore, as one of preferred embodiments of the polyimide composition, the present invention provides a polyimide composition (polyimide composition of embodiment A) containing the polyimide resin of the present invention, an epoxy compound having three or more epoxy groups in one molecule and having a glycidyl amine moiety, and an organic solvent. The polyimide composition of embodiment A contains an epoxy compound having three or more epoxy groups in one molecule and having a glycidylamine moiety in addition to the polyimide resin of the present invention, and thus a cured film of the polyimide composition having improved adhesion to inorganic compounds and metals can be formed. The epoxy compound having three or more epoxy groups in one molecule and having a glycidylamine moiety has excellent compatibility with the polyimide resin of the present invention or excellent solubility in the organic solvent used in the present invention due to the amine moiety, and is excellent in reactivity when heated and stability when not heated (storage stability as a polyimide composition), and the epoxy group can react with the amino group, carboxy group, acetamide group, etc. at the end of the polyimide resin. By bonding the epoxy compound to the end of the polyimide resin, the epoxy group of the epoxy compound is ring-opened to generate a large number of hydroxyl groups, and it is presumed that a cured film of the polyimide composition having improved adhesion to inorganic compounds and metals can be formed while taking advantage of the characteristics of the polyimide resin of the present invention, i.e., low dielectric tangent, high elastic modulus, and low linear thermal expansion coefficient. Furthermore, the polyimide composition of embodiment A can have improved mechanical properties such as tensile modulus as compared to the polyimide resin alone, due to the epoxy compound being bonded to the terminals of the polyimide resin.

[0073] Examples of epoxy compounds having three or more epoxy groups in one molecule and having a glycidyl amine moiety include epoxy compounds which are saturated or unsaturated aliphatic compounds, alicyclic compounds, aromatic compounds, heterocyclic compounds, or combinations thereof, and which have a glycidyl amine moiety and may further have a glycidyl ether moiety, and which are derived from a compound having two or more amino groups, or one or more amino groups and one or more hydroxyl groups.

[0074] Specific examples include epoxy compounds having a glycidyl amine moiety derived from a xylylenediamine such as meta-xylylenediamine or para-xylylenediamine, epoxy compounds having a glycidyl amine moiety derived from 1,3-bis(aminomethyl)cyclohexane, epoxy compounds having a glycidyl amine moiety derived from diaminodiphenylmethane, epoxy compounds having a glycidyl amine moiety and a glycidyl ether moiety derived from paraaminophenol, and epoxy compounds having a glycidyl amine moiety and a glycidyl ether moiety derived from 4-amino-3-methylphenol.

[0075] More specific examples include N,N,N',N'-tetraglycidylmeta-xylylenediamine, N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane, N,N,N',N'-tetraglycidyl-4,4-(4-aminophenyl)-p-diisopropylbenzene, 1,1,2,2-(tetraglycidyloxyphenyl)ethane, 1,1,2,2-tetrabis(hydroxyphenyl)ethane tetraglycidyl ether, tetraglycidyl-1,3-bisaminomethylcyclohexane, N-[2-methyl-4-(oxiranylmethoxy)phenyl]-N-(oxiranylmethyl)oxiranemethanamine, and the like. Among them, an epoxy compound containing a skeleton structure represented by the following chemical formula (I) in the molecule is more preferable.

[0076] [ka]

[0077] The epoxy compound used in the present invention, which has three or more epoxy groups in one molecule and has a glycidyl amine moiety, preferably contains one or more selected from the group consisting of an epoxy compound having a glycidyl amine moiety derived from meta-xylylenediamine, an epoxy compound having a glycidyl amine moiety derived from diaminodiphenylmethane, and an epoxy compound having a glycidyl amine moiety and a glycidyl ether moiety derived from 4-amino-3-methylphenol, from the viewpoints of compatibility and solubility, and more preferably contains one or more selected from the group consisting of an epoxy compound having a glycidyl amine moiety derived from meta-xylylenediamine, and an epoxy compound having a glycidyl amine moiety and a glycidyl ether moiety derived from 4-amino-3-methylphenol.

[0078] The epoxy compound used in the present invention can be produced by a conventionally known production method, and is obtained by reacting various alcohols, phenols, and amines with epihalohydrin. For example, an epoxy compound having a glycidylamine moiety derived from metaxylylenediamine can be obtained by adding epichlorohydrin to metaxylylenediamine.

[0079] As the epoxy compound having three or more epoxy groups in one molecule and having a glycidylamine moiety used in the present invention, from the viewpoints of compatibility and solubility, N,N,N',N'-tetraglycidylmeta-xylylenediamine represented by the following chemical formula (Ia), N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane represented by the following chemical formula (Ib), and N-[2-methyl-4-(oxiranylmethoxy)phenyl]-N-(oxiranylmethoxy)phenyl represented by the following chemical formula (Ic) are particularly preferred. and N-[2-methyl-4-(oxiranylmethoxy)phenyl]-N-(oxiranylmethyl)oxiranemethanamine represented by the following chemical formula (Ia): The epoxy compound used in the present invention may be a commercially available product appropriately selected and used. For example, Maxive M-100 polyepoxy resin (manufactured by Mitsubishi Gas Chemical Co., Ltd.), Sumiepoxy ELM-434 series, Sumiepoxy ELM-100 series (all manufactured by Sumitomo Chemical Co., Ltd.), etc. may be used.

[0080] [ka]

[0081] The epoxy compound having three or more epoxy groups in one molecule and having a glycidylamine moiety may be used alone or in combination of two or more kinds. The content of the epoxy compound having three or more epoxy groups in one molecule and having a glycidyl amine moiety may be appropriately selected depending on the balance between the desired adhesion and the desired physical properties, and is not particularly limited, but may be, for example, 5 parts by mass to 35 parts by mass, and preferably 10 parts by mass to 20 parts by mass, relative to 100 parts by mass of the polyimide resin of the present invention.

[0082] The polyimide composition of embodiment A may further contain a silane coupling agent in order to improve adhesion. As the silane coupling agent, a known silane coupling agent can be appropriately selected and used. The silane coupling agent used in the polyimide composition of embodiment A may be a compound represented by the following general formula (A) in order to further improve adhesion.

[0083] [ka] (In formula (A), R a represents a monovalent group containing at least one selected from the group consisting of a glycidyl group, a (meth)acryloyl group, an acid anhydride group, a hydroxy group, a triazine group, and an amino group; R b and R c are each independently an alkyl group having 1 to 5 carbon atoms, n is an integer of 1 to 10, and m is an integer of 1 to 3.

[0084] R b and R c may each independently be an alkyl group having 1 to 3 carbon atoms, and may be a methyl group or an ethyl group. n may be 1-5.

[0085] Examples of the compound represented by the following general formula (A) include hydroxymethyltrimethoxysilane, hydroxymethyltriethoxysilane, 2-hydroxyethyltrimethoxysilane, 2-hydroxyethyltriethoxysilane, 3-hydroxypropyltrimethoxysilane, 3-hydroxypropyltriethoxysilane, 4-hydroxybutyltrimethoxysilane, 4-hydroxybutyltriethoxysilane, glycidoxymethyltrimethoxysilane, glycidoxymethyltriethoxysilane, 2-glycidoxyethyltrimethoxysilane, 2-glycidoxyethyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 4-glycidoxybutyltrimethoxysilane, 4-glycidoxybutyltriethoxysilane, bis(2-hydroxymethyl)-3-aminopropyltriethoxysilane, bis(2 -hydroxymethyl)-3-aminopropyltrimethoxysilane, bis(2-glycidoxymethyl)-3-aminopropyltriethoxysilane, bis(2-hydroxymethyl)-3-aminopropyltrimethoxysilane, ureidomethyltrimethoxysilane, ureidomethyltriethoxysilane, 2-ureidoethyltrimethoxysilane, 2-ureidoethyltriethoxysilane, 3-ureidopropyltrimethoxysilane, 3-ureidopropyltriethoxysilane, 4-ureidobutyltrimethoxysilane, 4-ureidobutyltriethoxysilane, 3-trimethoxysilylpropylsuccinic anhydride, 3-(meth)acryloyloxypropyltrimethoxysilane, 3-(meth)acryloyloxypropyltriethoxysilane, 3-(meth)acryloyloxypropylmethyldimethoxysilane, and a compound represented by the following formula (a-1). The compound represented by the following formula (a-1) can be prepared by referring to JP-A-62-100462.

[0086] [ka] (In formula (a-1), R d represents -CH2CH2-S- or -CH2CH2-NH-; R b and Rc are each independently an alkyl group having 1 to 5 carbon atoms, n is an integer of 1 to 10, and m is an integer of 1 to 3.

[0087] The silane coupling agent used in the polyimide composition of embodiment A is a compound represented by the general formula (A) in which R a may represent a monovalent group containing at least one selected from the group consisting of a glycidyl group, a triazine group, and an amino group, may represent a monovalent group containing at least one selected from the group consisting of a glycidyl group and a triazine group, and may be a compound represented by formula (a-1).

[0088] The silane coupling agent may be used alone or in combination of two or more kinds. The content of the silane coupling agent may be appropriately selected depending on the balance between the desired adhesion and the desired physical properties, and is not particularly limited, but may be, for example, 0.1 parts by mass to 10 parts by mass, and preferably 0.5 parts by mass to 5 parts by mass, relative to 100 parts by mass of the polyimide resin of the present invention.

[0089] The polyimide composition of the present invention, including embodiment A, may further contain, in addition to the above-mentioned components, a photosensitive compound, a crosslinking agent, an antioxidant, a surfactant, a leveling agent, inorganic or organic fine particles, a rust inhibitor, and the like.

[0090] The polyimide composition can be prepared by dissolving the polyimide resin of the present invention described above in an organic solvent, and further dissolving or dispersing other components as required. The content of the polyimide resin in the polyimide composition may be appropriately selected depending on the application, etc., and is not particularly limited. The polyimide composition used for the cured film of the polyimide composition of the present invention described later may have a polyimide resin content of 5 mass % or more, 10 mass % or more, 30 mass % or less, or 25 mass % or less, relative to the total amount of the polyimide composition.

[0091] The viscosity of the polyimide composition is not particularly limited and may be appropriately selected depending on the application. The polyimide composition used in the method for producing a cured film of the polyimide composition of the present invention described below has a viscosity at 25°C, as measured with a rotational viscometer, of preferably 1000 mPa s or more, more preferably 3000 mPa s or more, and preferably 50,000 mPa s or less, more preferably 30,000 mPa s or less. The viscosity of the polyimide composition can be measured at 25° C. using a single cylinder type rotational viscometer (for example, TVB-10 type viscometer manufactured by Toki Sangyo Co., Ltd.) according to the method described in JIS K7117-1.

[0092] III. Cured film of polyimide composition The present invention provides a cured film of a polyimide composition obtained by curing the polyimide composition of the present invention. The cured film of the polyimide composition according to the present invention contains the polyimide resin contained in the polyimide composition according to the present invention, the solid contents of other components, and reaction products thereof.

[0093] The cured film of the polyimide composition of the present invention may have a dielectric constant of 3.60 or less, 3.30 or less, 3.20 or less, or even 3.00 or less at a frequency of 10 GHz according to JIS R1641 from the viewpoint of reducing electric signal loss when used as a semiconductor packaging material, etc. Furthermore, the cured film of the polyimide composition of the present invention may have a dielectric loss tangent of 0.020 or less, 0.015 or less, or 0.012 or less at a frequency of 10 GHz according to JIS R1641 from the viewpoint of reducing electric signal loss when used as a semiconductor packaging material, etc. The dielectric constant and dielectric loss tangent of the cured film of the polyimide composition can be measured by the split cylinder method in accordance with JIS R1641 using a split cylinder resonator device (CR-710, manufactured by Kanto Electronics Application Development Co., Ltd.) at a measurement frequency of 10 GHz. As a pretreatment, the test pieces to be used for the measurements are dried in an oven at 110°C for 30 minutes, and then conditioned for 24 hours in an environmental test chamber (SH-662, manufactured by Espec Corporation) at 23°C and 50% humidity. The dielectric constant and dielectric loss tangent are measured immediately after removing the test pieces from the environmental test chamber.

[0094] The linear thermal expansion coefficient of the cured film of the polyimide composition of the present invention may be 30 ppm or less, 27 ppm or less, 25 ppm or less, or 20 ppm or less from the viewpoint of dimensional stability when used as a semiconductor packaging material, etc. Here, the linear thermal expansion coefficient in the present invention can be calculated from a TMA curve obtained by heating the material to 30°C to 400°C at a heating rate of 10°C / min with a load of 9 g using a thermomechanical analyzer (for example, a thermomechanical analyzer (TMA-60), manufactured by Shimadzu Corporation). The linear thermal expansion coefficient is calculated as an average value between 100 and 150°C.

[0095] The cured film of the polyimide composition of the present invention may have a tensile modulus of elasticity of 4.5 GPa or more, or 5.0 GPa or more at 25° C. In this way, a high tensile modulus at 25° C. (room temperature) is advantageous in terms of the physical stability of the package when used in a new semiconductor package that vertically integrates multiple semiconductor packages. On the other hand, the tensile modulus may be 10.0 GPa or less in terms of concerns about brittle fracture. The tensile test can be carried out in accordance with JIS K7127 using a tensile tester (e.g., Shimadzu Corporation: Autograph AG-X 1N, load cell: SBL-1KN) by cutting a test piece of 10 mm width x 150 mm length from the cured film of the polyimide composition, at 25°C, at a stretching speed of 50 mm / min, and with a gripper distance of 100 mm. The tensile modulus can be determined from the initial gradient of the stress-strain curve. The cured film of the polyimide composition when carrying out the tensile test may have a thickness of 35 μm to 55 μm.

[0096] A cured film of the polyimide composition of the present invention, particularly a cured film of the polyimide composition of embodiment A, may have adhesion to a silicon nitride substrate such that the number of unpeeled cross cuts in a cross cut test in accordance with JIS K 5400-8.5 is 80% or more, 90% or more, or even 100%. A cured film of the polyimide composition of the present invention, particularly a cured film of the polyimide composition of embodiment A, may have adhesion to a copper substrate such that the number of unpeeled cross cuts in a cross cut test in accordance with JIS K 5400-8.5 is 80% or more, 90% or more, or even 100%.

[0097] The thickness of the cured film of the polyimide composition of the present invention may be appropriately selected depending on the application and is not particularly limited, but may be 1 μm or more, 20 μm or more, 30 μm or more, or 40 μm or more, while it may be 100 μm or less, 70 μm or less, or 50 μm or less.

[0098] The cured film of the polyimide composition of the present invention may be subjected to a surface treatment such as saponification treatment, glow discharge treatment, corona discharge treatment, ultraviolet treatment, or flame treatment.

[0099] [Method for producing a cured film of a polyimide composition] The method for producing a cured film of the polyimide composition of the present invention is not particularly limited as long as it is a method capable of producing a cured film of the polyimide composition of the present invention. The method for producing a cured film of the polyimide composition of the present invention includes the following steps: applying the polyimide composition onto a substrate and drying the composition to form a coating film; The method for producing a cured film of a polyimide composition includes a step of heating the coating film to form a cured film.

[0100] The substrate used in the step of forming the coating film is not particularly limited. For example, the substrate may be a glass substrate, a semiconductor substrate such as a Si substrate (silicon wafer), a metal oxide insulating substrate such as a TiO2 substrate or a SiO2 substrate, a silicon nitride substrate, a copper substrate, a copper alloy substrate, a composite substrate in which a resin film such as a polyimide film is laminated on the substrate, or a substrate in which a circuit component material is arranged on the substrate.

[0101] The coating means is not particularly limited as long as it is a method capable of coating with a desired film thickness, and for example, known means such as a spin coater, die coater, comma coater, roll coater, gravure coater, curtain coater, spray coater, and lip coater can be used.

[0102] After the polyimide composition is applied to the substrate, it is dried to form a coating film. The drying temperature is less than 150° C., preferably 30° C. or higher and 140° C. or lower.

[0103] The drying time may be adjusted appropriately depending on the thickness of the coating film of the polyimide composition, the type of solvent, the drying temperature, etc., but is usually 5 to 60 minutes, preferably 10 to 40 minutes. If it exceeds the upper limit, it is not preferable from the viewpoint of the production efficiency of the cured film of the polyimide composition. On the other hand, if it is below the lower limit, the sudden drying of the solvent may affect the appearance of the cured film of the polyimide composition obtained.

[0104] The method for drying the solvent is not particularly limited as long as it is possible to dry the solvent at the above-mentioned temperature. For example, an oven, a drying furnace, a hot plate, infrared heating, or the like can be used. The atmosphere during drying of the solvent may be either air or an inert gas atmosphere.

[0105] The coating film is heated to form a cured film. The temperature to which the coating film is heated may be 150°C or higher and 240°C or lower, 170°C or higher and 235°C or lower, or 200°C or higher and 230°C or lower, from the viewpoints of accelerating the curing reaction and heat resistance of other semiconductor packaging materials such as encapsulants. The heating means used for forming the cured film may be the same as that used for drying described above. The coating may be heated in air or in an inert gas atmosphere.

[0106] The heating time may be appropriately adjusted depending on the thickness of the coating film, but is usually from 10 minutes to 2 hours, preferably from 30 minutes to 1 hour.

[0107] In addition, when the polyimide composition contains a photosensitive component, a patterned coating film may be formed by carrying out patterned exposure after formation of the coating film and appropriately developing the same, and then the patterned coating film may be heated to form a patterned cured film.

[0108] The use of the cured film of the polyimide composition of the present invention is not particularly limited, but since it has a low dielectric constant, a low dielectric loss tangent, a high elastic modulus, and a low coefficient of linear thermal expansion, and further has high adhesion, it can be suitably used, for example, in semiconductor electronic components or semiconductor devices, specifically, as a passivation film for semiconductors, a surface protective film for semiconductor elements, an interlayer insulating film, an interlayer insulating film for multilayer wiring for high-density mounting, an insulating film for organic electroluminescent elements, etc. In addition, the cured film of the polyimide composition of the present invention can also be applied to members for image display devices such as liquid crystal display devices and organic EL display devices, members for touch panels, flexible printed circuit boards, members for solar cell panels such as surface protective films and substrate materials, members for optical waveguides, other semiconductor-related members, etc.

[0109] IV. Insulating films, protective films, and electronic components

[0110] The present invention provides an insulating film formed using a cured film of the polyimide composition according to the present invention. The present invention also provides a protective film formed using a cured film of the polyimide composition according to the present invention. The present invention also provides an electronic component including the insulating film according to the present invention or the protective film according to the present invention.

[0111] The insulating film or protective film may be a film having both the functions of an insulating film and a protective film, and can be used, for example, as an interlayer insulating film for a rewiring layer, a passivation film, a buffer coat film, a surface protective film, or the like.

[0112] By using one or more films selected from the group consisting of the above passivation films, buffer coat films, interlayer insulating films, and surface protection films, it is possible to manufacture highly reliable electronic components such as semiconductor devices, multilayer wiring boards, and various electronic devices.

[0113] An example of a manufacturing process for a semiconductor device, which is an electronic component of the present invention, will be described with reference to the drawings. FIG. 1 is a manufacturing process diagram of a semiconductor device having a multilayer wiring structure, which is an electronic component according to one embodiment of the present invention. 1A, a semiconductor substrate 1 such as a Si substrate having circuit elements is covered with a protective film 2 such as a silicon oxide film except for a predetermined portion of the circuit elements, and a first conductor layer 3 is formed on the exposed circuit elements. Then, an interlayer insulating film 4 is formed on the semiconductor substrate 1.

[0114] Next, as shown in FIG. 1B, a photosensitive resin layer 5 is formed on the interlayer insulating film 4, and windows 6A are provided by known photolithography techniques so that predetermined portions of the interlayer insulating film 4 are exposed.

[0115] As shown in FIG. 1C, the interlayer insulating film 4 from which the window 6A is exposed is selectively etched by a suitable known method to provide a window 6B. Next, the photosensitive resin layer 5 is removed using an etching solution that corrodes the photosensitive resin layer 5 without corroding the first conductor layer 3 exposed through the window 6B.

[0116] As shown in FIG. 1(D), a second conductor layer 7 is formed by using a known photolithography technique, and is electrically connected to the first conductor layer 3. When forming a multi-layer wiring structure having three or more layers, the above steps can be repeated to form each layer.

[0117] 1(E), the polyimide composition of the present invention is used to form a cured film of the polyimide composition, and a window 6C is opened by a laser or the like to form a surface protective film 8. Alternatively, when the polyimide composition of the present invention contains a photosensitive component and is a photosensitive composition, a coating film of the polyimide composition may be formed, and a window 6C may be opened by pattern exposure to form a cured film to form the surface protective film 8. The surface protective film 8 protects the second conductor layer 7 from external stress, α-rays, and the like, and the resulting semiconductor device has excellent reliability. In the above example, the interlayer insulating film may be formed using the polyimide composition of the present invention. EXAMPLES

[0118] [Evaluation method] Unless otherwise specified, measurements and evaluations were performed at 25° C. Room temperature refers to 25° C. The film specimens were cut near the center of the film.

[0119] <Weight average molecular weight of polyimide> Polyimide was dissolved in N-methylpyrrolidone (NMP) at a concentration of 0.5% by mass, and the solution was filtered through a syringe filter (pore size: 0.45 μm). A 10 mmol% LiBr-NMP solution was used as a developing solvent, and a GPC apparatus (HLC-8120 manufactured by Tosoh, detector: refractive index (RID) detector, column used: GPC LF-804 manufactured by SHODEX) was used, and the measurement was performed under the conditions of sample injection amount 50 μL, solvent flow rate 0.4 mL / min, column temperature 37 ° C., and detector temperature 37 ° C. The weight average molecular weight of polyimide was expressed as a converted value relative to standard polystyrene measured based on polystyrene standard samples (weight average molecular weights: 364,700, 204,000, 103,500, 44,360, 27,500, 13,030, 6,300, 3,070) of the same concentration as the sample. The elution time was compared with a calibration curve to determine the weight average molecular weight.

[0120] <Confirmation of imidization rate of polyimide( 1 H NMR) Approximately 10 mg of polyimide was dissolved in 0.75 mL of deuterated dimethyl sulfoxide containing 0.03 vol% tetramethylsilane (TMS), and the polyimide was analyzed using a Fourier transform nuclear magnetic resonance apparatus (AVANCE400, manufactured by Bruker). 1 Measurements were performed for H nuclei with an accumulation count of 256. The chemical shifts were based on TMS (0 ppm), and a signal derived from the carboxy protons of polyamic acid (around 13 ppm) and an amide proton (around 11 ppm) were confirmed.

[0121] <Evaluation of re-dissolving ability of polyimide coating film> A piece of glass measuring 20 mm in width, 50 mm in length and 0.5 mm in thickness was inserted 25 mm into the prepared polyimide composition with its long side perpendicular, then pulled out, and the polyimide composition attached to the glass surface was air-dried in a local exhaust device at 25°C for 15 hours to prepare a coating film (air-dried film). A 20 mm x 20 mm test piece was cut out from the coating film, and the test piece was placed in a glass vial containing 20 mL of cyclopentanone, followed by stirring at 100 rpm with a magnetic stirrer, and the time until the coating film was completely dissolved was measured. (Evaluation Criteria) ○: Dissolution time is 15 minutes or less △: Dissolution time is between 15 minutes and 30 minutes ×: Dissolution time exceeds 30 minutes

[0122] <Method for measuring thickness of cured film> The film thickness of a test piece of the cured film of the polyimide composition cut into a size of 100 mm x 100 mm was measured at a total of five points, namely, the four corners and the center, using a digital linear gauge (manufactured by Ozaki Manufacturing Co., Ltd., model PDN12 digital gauge), and the average of the measured values ​​was regarded as the film thickness of the cured film of the polyimide composition.

[0123] <Thermal property evaluation: Linear thermal expansion coefficient> A test piece of the cured film of the polyimide composition cut to a size of 5 mm x 10 mm was used to obtain a TMA curve with a thermomechanical analyzer (TMA-60, manufactured by Shimadzu Corporation) when the temperature was raised from 30°C to 400°C at a rate of 10°C / min under a load of 9 g. The linear thermal expansion coefficient was determined as an average value in the range of 100 to 150°C.

[0124] <Electrical property evaluation: dielectric constant, dielectric loss tangent> Using a test piece of the cured film of the polyimide composition cut into a size of 70 mm × 70 mm, the dielectric constant and dielectric loss tangent were measured by the split cylinder method in accordance with JIS R1641 using a split cylinder resonator device (CR-710, manufactured by Kanto Electronics Application Development Co., Ltd.) at a measurement frequency of 10 GHz. The test pieces used for the measurements were dried in an oven at 110°C for 30 minutes before the measurements, and then conditioned for 24 hours in an environmental test chamber SH-662 (manufactured by Espec Corp.) at 23°C and 50% humidity. They were then removed from the chamber and immediately subjected to the measurements.

[0125] <Mechanical property evaluation (tensile test): Tensile modulus> The tensile test was performed in accordance with JIS K7127 using a test piece of the cured film of the polyimide composition cut into a size of 10 mm in width × 150 mm in length, with a tensile tester (e.g., Shimadzu Corporation: Autograph AG-X 1N, load cell: SBL-1KN) at 25°C, a stretching speed of 50 mm / min, and a gripping distance of 100 mm. The tensile modulus was determined from the initial slope of the stress-strain curve.

[0126] <Adhesion evaluation: Cross-cut test> The test was conducted in accordance with JIS K5400-8.5 cross-cut test. After the test, the number of cross-cuts (squares) of the cured film that remained on the substrate without peeling (number of remaining squares) out of a total of 100 squares was counted. The silicon nitride substrate was a SiN 100 nm Si substrate manufactured by Assist Navi Co., Ltd., and the copper substrate was a Cu 100 nm / Ti 50 nm Si substrate manufactured by Assist Navi Co., Ltd. The substrate was immersed in isopropyl alcohol, ultrasonically cleaned for 5 minutes, and then dried before being used to produce a cured film of the polyimide composition.

[0127] Example 1 (1) Synthesis of polyimide resin With reference to Synthesis Example 1 of Japanese Patent No. 6165153, a tetracarboxylic dianhydride (TMPBP-TME) represented by the following chemical formula (1-1) was synthesized.

[0128] [ka]

[0129] In a nitrogen atmosphere, dehydrated N,N-dimethylacetamide (DMAc) (300 g) and 2,2'-bis(trifluoromethyl)benzidine (TFMB) (20.79 g, 64.9 mmol) were placed in a 500 mL separable flask, and the mixture was stirred at room temperature to dissolve TFMB. TMPBP-TME (25.45 g, 41.1 mmol), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) (4.14 g, 12.9 mmol), and pyromellitic anhydride (PMDA) (2.24 g, 10.3 mmol) were added to the above solution in several portions, and the mixture was stirred at room temperature for 15 hours to obtain a polyimide precursor solution (solid content about 15 mass%) in which the polyimide precursor (polyamic acid) was dissolved. A mixed solution of 25.50 g of acetic anhydride and 0.99 g of pyridine was slowly added dropwise to the obtained polyimide precursor solution at room temperature, and after the dropwise addition was completed, the mixture was stirred for an additional 15 hours to obtain a polyimide solution (solid content: approximately 15% by mass). The resulting polyimide solution was diluted with DMAc to a solid content of about 5% by mass, and then slowly dropped into a large amount of isopropyl alcohol while stirring to precipitate the polyimide. The resulting precipitate was filtered, washed with isopropyl alcohol, and then dried at 110°C for 8 hours in a vacuum dryer to obtain polyimide resin 1. Regarding the obtained polyimide resin 1 1 1 H NMR measurement confirmed that the signals derived from the carboxy proton and amide proton of the polyamic acid had disappeared, that is, it was confirmed that the imidization had progressed completely.

[0130] (2) Preparation of polyimide composition A solvent (a mixed solvent of DMAc and ethyl acetate (EA) in a weight ratio of 1:1) was added to the obtained polyimide resin 1, and the mixture was stirred at room temperature to dissolve the polyimide, thereby preparing a homogeneous solution with a polyimide concentration of 10% by mass. This solution was pressure filtered using a 400-mesh wire screen to obtain a polyimide composition 1.

[0131] (3) Preparation of a cured film of a polyimide composition The obtained polyimide composition was spin-coated onto a glass substrate having a polyimide film (UPILEX 125S, manufactured by Ube Industries, Ltd.) attached thereto. The spin-coating conditions were adjusted so that the thickness of the cured film of the polyimide composition finally obtained was about 40 to 50 μm. After the polyimide composition was spin-coated, the substrate was heated on a hot plate to dry off the solvent (heating at 40° C. for 8 minutes, then at 80° C. for 8 minutes, and then at 130° C. for 8 minutes). After drying, the substrate was placed in an oven and heat-treated at 230° C. in air for 1 hour, and then allowed to cool to room temperature, after which the cured film of the polyimide composition was peeled off from the substrate. The evaluation results of the cured film of the resulting polyimide composition are shown in Table 1.

[0132] Example 2 In the synthesis of the polyimide resin of Example 1, the amounts of TFMB, TMPBP-TME, BTDA, and PMDA were changed to 20.63 g (64.4 mmol), 24.85 g (40.2 mmol), 6.16 g (19.1 mmol), and 0.97 g (4.46 mmol), and 26.31 g of acetic anhydride and 1.02 g of pyridine were used. The polyimide resin was synthesized in the same manner as in Example 1, and polyimide resin 2 was obtained. Regarding the obtained polyimide resin 2, 1 1 H NMR measurement confirmed that the signals derived from the carboxy proton and amide proton of the polyamic acid had disappeared, that is, it was confirmed that the imidization had progressed completely. A cured film of a polyimide composition was produced in the same manner as in Example 1, except that polyimide resin 2 was used instead of polyimide resin 1 in Example 1. The evaluation results of the obtained cured film of the polyimide composition are shown in Table 1.

[0133] Example 3 In the synthesis of the polyimide resin of Example 1, the amounts of TFMB, TMPBP-TME, BTDA, and PMDA were changed to 22.00 g (68.7 mmol), 18.96 g (30.6 mmol), 10.96 g (34.0 mmol), and 0.74 g (3.40 mmol), and 28.06 g of acetic anhydride and 1.09 g of pyridine were used. The polyimide resin was synthesized in the same manner as in Example 1, and polyimide resin 3 was obtained. Regarding the obtained polyimide resin 3, 1 1 H NMR measurement confirmed that the signals derived from the carboxy proton and amide proton of the polyamic acid had disappeared, that is, it was confirmed that the imidization had progressed completely. A cured film of the polyimide composition was produced in the same manner as in Example 1, except that polyimide resin 3 was used instead of polyimide resin 1 in Example 1. The evaluation results of the obtained cured film of the polyimide composition are shown in Table 1.

[0134] Example 4 In the synthesis of the polyimide resin of Example 1, the amounts of TFMB, TMPBP-TME, BTDA, and PMDA were changed to 21.36 g (66.7 mmol), 22.87 g (37.0 mmol), 6.38 g (19.8 mmol), and 2.02 g (9.24 mmol), and 27.24 g of acetic anhydride and 1.06 g of pyridine were used. The polyimide resin was synthesized in the same manner as in Example 1, and polyimide resin 4 was obtained. Regarding the obtained polyimide resin 4, 1 1 H NMR measurement confirmed that the signals derived from the carboxy proton and amide proton of the polyamic acid had disappeared, that is, it was confirmed that the imidization had progressed completely. A cured film of a polyimide composition was produced in the same manner as in Example 1, except that polyimide resin 4 was used instead of polyimide resin 1 in Example 1. The evaluation results of the obtained cured film of the polyimide composition are shown in Table 1. For the evaluation of adhesion, the substrate was changed to a silicon nitride substrate, and a cured film of the polyimide composition was produced on the silicon nitride substrate in the same manner as in Example 1. The cured film of the polyimide composition was not peeled off from the substrate, and the adhesion evaluation was performed. The results of the adhesion evaluation are shown in Table 2.

[0135] Comparative Example 1 A polyimide resin was synthesized in the same manner as in Example 1, except that in the synthesis of the polyimide resin in Example 1, 18.18 g (56.8 mmol) of TFMB, 34.76 g (56.2 mmol) of TMPBP-TME as the tetracarboxylic dianhydride, 23.18 g of acetic anhydride, and 0.90 g of pyridine were used, to obtain a comparative polyimide resin 1. 1 1 H NMR measurement confirmed that the signals derived from the carboxy proton and amide proton of the polyamic acid had disappeared, that is, it was confirmed that the imidization had progressed completely. A cured film of a polyimide composition was produced in the same manner as in Example 1, except that Comparative Polyimide Resin 1 was used instead of Polyimide Resin 1 in Example 1. The evaluation results of the obtained cured film of the polyimide composition are shown in Table 1.

[0136] Comparative Example 2 In the synthesis of the polyimide resin of Example 1, the amount of TFMB was changed to 18.86 g (58.9 mmol), the amount of TMPBP-TME as the tetracarboxylic dianhydride was changed to 32.46 g (52.5 mmol), the amount of PMDA was changed to 1.27 g (5.83 mmol), and the amount of acetic anhydride was changed to 24.05 g and pyridine to 0.93 g. A polyimide resin was synthesized in the same manner as in Example 1, and a comparative polyimide resin 2 was obtained. Regarding the obtained comparative polyimide resin 2, 1 1 H NMR measurement confirmed that the signals derived from the carboxy proton and amide proton of the polyamic acid had disappeared, that is, it was confirmed that the imidization had progressed completely. A cured film of a polyimide composition was produced in the same manner as in Example 1, except that Comparative Polyimide Resin 2 was used instead of Polyimide Resin 1 in Example 1. The evaluation results of the obtained cured film of the polyimide composition are shown in Table 1.

[0137] Comparative Example 3 In the synthesis of the polyimide resin of Example 1, the amount of TFMB was changed to 18.86 g (58.9 mmol), the amount of TMPBP-TME as the tetracarboxylic dianhydride was changed to 31.15 g (50.4 mmol), the amount of PMDA was changed to 1.22 g (5.56 mmol), and the amounts of acetic anhydride and pyridine were changed to 24.05 g and 0.93 g, respectively. A polyimide resin was synthesized in the same manner as in Example 1, and comparative polyimide resin 3 was obtained. Regarding the obtained comparative polyimide resin 3, 1 1 H NMR measurement confirmed that the signals derived from the carboxy proton and amide proton of the polyamic acid had disappeared, that is, it was confirmed that the imidization had progressed completely. A cured film of the polyimide composition was produced in the same manner as in Example 1, except that Comparative Polyimide Resin 3 was used instead of Polyimide Resin 1 in Example 1. The evaluation results of the obtained cured film of the polyimide composition are shown in Table 1.

[0138] Comparative Example 4 In the synthesis of the polyimide resin of Example 1, the amount of TFMB was changed to 20.06 g (62.6 mmol), the amount of TMPBP-TME as the tetracarboxylic dianhydride was changed to 31.43 g (50.7 mmol), the amount of PMDA was changed to 1.22 g (5.63 mmol), and the amount of acetic anhydride was changed to 25.58 g and pyridine to 0.99 g. The polyimide resin was synthesized in the same manner as in Example 1, and comparative polyimide resin 4 was obtained. Regarding the obtained comparative polyimide resin 4, 1 1 H NMR measurement confirmed that the signals derived from the carboxy proton and amide proton of the polyamic acid had disappeared, that is, it was confirmed that the imidization had progressed completely. A cured film of the polyimide composition was produced in the same manner as in Example 1, except that Comparative Polyimide Resin 4 was used instead of Polyimide Resin 1 in Example 1. The evaluation results of the obtained cured film of the polyimide composition are shown in Table 1.

[0139] Comparative Example 5 In the synthesis of the polyimide resin of Example 1, the amounts of TFMB used were changed to 19.75 g (61.7 mmol), TMPBP-TME used as the tetracarboxylic dianhydride to 23.79 g (38.4 mmol), 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA) to 8.14 g (18.3 mmol), and PMDA to 0.93 g (4.27 mmol), and the amounts of acetic anhydride used were changed to 25.19 g and pyridine to 0.98 g. A polyimide resin was synthesized in the same manner as in Example 1, and comparative polyimide resin 5 was obtained. Regarding the comparative polyimide resin 5 obtained, 1 1 H NMR measurement confirmed that the signals derived from the carboxy proton and amide proton of the polyamic acid had disappeared, that is, it was confirmed that the imidization had progressed completely. A cured film of a polyimide composition was produced in the same manner as in Example 1, except that Comparative Polyimide Resin 5 was used instead of Polyimide Resin 1 in Example 1. The evaluation results of the obtained cured film of the polyimide composition are shown in Table 1.

[0140] Comparative Example 6 In the synthesis of the polyimide resin of Example 1, the amount of TFMB was changed to 20.39 g (63.7 mmol), the amount of TMPBP-TME as the tetracarboxylic dianhydride was changed to 17.54 g (28.4 mmol), the amount of 6FDA was changed to 14.00 g (31.5 mmol), and the amount of PMDA was changed to 0.74 g (3.40 mmol), and the amount of acetic anhydride was changed to 26.00 g and pyridine to 1.01 g. A polyimide resin was synthesized in the same manner as in Example 1, and comparative polyimide resin 6 was obtained. Regarding the obtained comparative polyimide resin 6, 1 1 H NMR measurement confirmed that the signals derived from the carboxy proton and amide proton of the polyamic acid had disappeared, that is, it was confirmed that the imidization had progressed completely. A cured film of a polyimide composition was produced in the same manner as in Example 1, except that Comparative Polyimide Resin 6 was used instead of Polyimide Resin 1 in Example 1. The evaluation results of the obtained cured film of the polyimide composition are shown in Table 1.

[0141] Comparative Example 7 In the synthesis of the polyimide resin of Example 1, the amount of TFMB was changed to 19.42 g (60.6 mmol), the amount of TMPBP-TME as the tetracarboxylic dianhydride was changed to 30.08 g (48.6 mmol), the amount of BTDA was changed to 1.93 g (6.00 mmol), and the amount of PMDA was changed to 1.18 g (5.40 mmol), and 24.77 g of acetic anhydride and 0.96 g of pyridine were used. A polyimide resin was synthesized in the same manner as in Example 1, and comparative polyimide resin 7 was obtained. Regarding the obtained comparative polyimide resin 7, 1 1 H NMR measurement confirmed that the signals derived from the carboxy proton and amide proton of the polyamic acid had disappeared, that is, it was confirmed that the imidization had progressed completely. A cured film of a polyimide composition was produced in the same manner as in Example 1, except that Comparative Polyimide Resin 7 was used instead of Polyimide Resin 1 in Example 1. The evaluation results of the obtained cured film of the polyimide composition are shown in Table 1.

[0142] [Table 1]

[0143] [Summary of Table 1] It was shown that all of the polyimide resins of Examples 1 to 4, which are the polyimide resins of the present invention, are polyimide resins capable of forming cured films having a low dielectric constant, a low dielectric tangent, a high elastic modulus, and a low coefficient of linear thermal expansion, while providing coating films with a fast re-dissolving rate. In contrast, the polyimide resin of Comparative Example 1, which corresponds to the polyimide resin described in Patent Document 2, was a polyimide resin with a slow re-dissolving rate of the coating film. The polyimide resin of Comparative Example 2, in which part of the carboxylic dianhydride component of the polyimide resin of Comparative Example 1 was replaced with rigid PMDA, was a polyimide resin with a slow re-dissolving rate of the coating film, similar to Comparative Example 1. The polyimide resin of Comparative Example 3, in which the molecular weight of the polyimide resin of Comparative Example 2 was reduced to about half, showed an increased re-dissolving rate of the coating film, but the mechanical properties of the cured film were deteriorated. The polyimide resin of Comparative Example 4, in which the molecular weight of the polyimide resin of Comparative Example 2 was reduced to about 1 / 5, gave a cured film that was very brittle and was unable to form a free-standing film. The polyimide resin of Comparative Example 5, in which 6FDA was used instead of BTDA of Example 2, showed a significant deterioration in the mechanical properties of the cured film, and also showed a poor linear thermal expansion coefficient. The polyimide resin of Comparative Example 6, in which 6FDA was used instead of BTDA of Example 3, also resulted in a cured film with deteriorated mechanical properties. The polyimide resin of Comparative Example 7, which had a high content of TMPBP-TME, was still a polyimide resin that had a slow re-dissolving rate of the coating film even though it contained the BTDA component.

[0144] Example 5 A polyimide composition was prepared and a cured film of the polyimide composition was produced in the same manner as in Example 1, except that polyimide resin 4 was used instead of polyimide resin 1 in Example 1, and 10 parts by mass of an epoxy compound having four epoxy groups in one molecule and having a glycidyl amine moiety (Maxive M-100 (MXV-M100), N,N,N',N'-tetraglycidyl metaxylylenediamine represented by the above chemical formula (Ia), manufactured by Mitsubishi Gas Chemical Company) was added as an additive, relative to 100 parts by mass of the polyimide resin. For the evaluation of adhesion, the substrate was changed to a silicon nitride substrate and a copper substrate, and a cured film of the polyimide composition was produced on each substrate in the same manner as in Example 1. The cured film of the polyimide composition was not peeled off from each substrate, and the adhesion evaluation was performed.

[0145] Example 6 A polyimide composition was prepared and a cured film of the polyimide composition was produced in the same manner as in Example 1, except that polyimide resin 4 was used instead of polyimide resin 1 in Example 1, and 10 parts by mass of an epoxy compound having four epoxy groups in one molecule and having a glycidylamine moiety (Sumiepoxy ELM-434 (ELM-434), N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane represented by the above chemical formula (Ib), manufactured by Sumitomo Chemical) was added as an additive, relative to 100 parts by mass of the polyimide resin. For the evaluation of adhesion, the substrate was changed to a silicon nitride substrate and a copper substrate, and a cured film of the polyimide composition was produced on each substrate in the same manner as in Example 1. The cured film of the polyimide composition was not peeled off from each substrate, and the adhesion evaluation was performed.

[0146] Example 7 A polyimide composition was prepared in the same manner as in Example 1, except that polyimide resin 4 was used instead of polyimide resin 1 in Example 1, and an epoxy compound having three epoxy groups in one molecule and having a glycidyl amine moiety and a glycidyl ether moiety (Sumiepoxy ELM-100 (ELM-100), N-[2-methyl-4-(oxiranylmethoxy)phenyl]-N-(oxiranylmethyl)oxiranemethanamine represented by the above chemical formula (Ic), manufactured by Sumitomo Chemical Co., Ltd.) was added as an additive in an amount of 10 parts by mass per 100 parts by mass of the polyimide resin, and a cured film of the polyimide composition was produced. For the evaluation of adhesion, the substrate was changed to a silicon nitride substrate and a copper substrate, and a cured film of the polyimide composition was produced on each substrate in the same manner as in Example 1. The cured film of the polyimide composition was not peeled off from each substrate, and the adhesion evaluation was performed. Example 8 A polyimide composition was prepared and a cured film of the polyimide composition was produced in the same manner as in Example 1, except that polyimide resin 4 was used instead of polyimide resin 1 in Example 1, and 10 parts by mass of an epoxy compound having four epoxy groups in one molecule and having a glycidylamine moiety (Maxive M-100 (MXV-M100), manufactured by Mitsubishi Gas Chemical Co., Ltd.) and 1 part by mass of 3-glycidoxypropylmethyldimethoxysilane (KBM-402, manufactured by Shin-Etsu Chemical Co., Ltd.) were added as additives relative to 100 parts by mass of the polyimide resin. For the evaluation of adhesion, the substrate was changed to a silicon nitride substrate and a copper substrate, and a cured film of the polyimide composition was produced on each substrate in the same manner as in Example 1. The cured film of the polyimide composition was not peeled off from each substrate, and the adhesion evaluation was performed.

[0147] Example 9 A polyimide composition was prepared in the same manner as in Example 1, except that polyimide resin 4 was used instead of polyimide resin 1 in Example 1, and 10 parts by mass of an epoxy compound having four epoxy groups in one molecule and having a glycidylamine moiety (Maxive M-100 (MXV-M100), manufactured by Mitsubishi Gas Chemical Co., Ltd.) and 1 part by mass of a silane coupling agent having the following structure (VD-5, manufactured by Shikoku Kasei Co., Ltd.) were added as additives relative to 100 parts by mass of the polyimide resin, relative to 100 parts by mass of the polyimide resin. A cured film of the polyimide composition was produced in the same manner as in Example 1. For the evaluation of adhesion, the substrate was changed to a silicon nitride substrate and a copper substrate, and a cured film of the polyimide composition was produced on each substrate in the same manner as in Example 1. The cured film of the polyimide composition was not peeled off from each substrate, and the adhesion evaluation was performed.

[0148] [ka]

[0149] Example 10 In Example 1, the solvent was changed from a 1:1 mixed solvent of DMAc and EA to cyclopentanone (CPN), polyimide resin 4 was used instead of polyimide resin 1, and 10 parts by mass of an epoxy compound having four epoxy groups in one molecule and having a glycidylamine moiety (Maxive M-100 (MXV-M100), manufactured by Mitsubishi Gas Chemical Co., Ltd.) and 1 part by mass of the silane coupling agent (VD-5, manufactured by Shikoku Kasei Co., Ltd.) were added as additives relative to 100 parts by mass of polyimide resin. A polyimide composition was prepared in the same manner as in Example 1, and a cured film of the polyimide composition was produced. For the evaluation of adhesion, the substrate was changed to a silicon nitride substrate and a copper substrate, and a cured film of the polyimide composition was produced on each substrate in the same manner as in Example 1. The cured film of the polyimide composition was not peeled off from each substrate, and the adhesion evaluation was performed.

[0150] Example 11 A polyimide composition was prepared and a cured film of the polyimide composition was produced in the same manner as in Example 10, except that the additive in Example 10 was changed from an epoxy compound having four epoxy groups in one molecule and having a glycidylamine moiety (Maxive M-100 (MXV-M100), manufactured by Mitsubishi Gas Chemical) to an epoxy compound having four epoxy groups in one molecule and having a glycidylamine moiety (Sumiepoxy ELM-434 (ELM-434), manufactured by Sumitomo Chemical). For the evaluation of adhesion, the substrate was changed to a silicon nitride substrate and a copper substrate, and a cured film of the polyimide composition was produced on each substrate in the same manner as in Example 1. The cured film of the polyimide composition was not peeled off from each substrate, and the adhesion evaluation was performed.

[0151] Example 12 A polyimide composition was prepared and a cured film of the polyimide composition was produced in the same manner as in Example 10, except that the additive in Example 10 was changed from an epoxy compound having four epoxy groups in one molecule and having a glycidyl amine moiety (Maxive M-100 (MXV-M100), manufactured by Mitsubishi Gas Chemical) to an epoxy compound having three epoxy groups in one molecule and having a glycidyl amine moiety and a glycidyl ether moiety (Sumiepoxy ELM-100 (ELM-100), manufactured by Sumitomo Chemical). For the evaluation of adhesion, the substrate was changed to a silicon nitride substrate and a copper substrate, and a cured film of the polyimide composition was produced on each substrate in the same manner as in Example 1. The cured film of the polyimide composition was not peeled off from each substrate, and the adhesion evaluation was performed.

[0152] [Table 2]

[0153] [Summary of Table 2] It was demonstrated that all of the polyimide compositions of the present invention, that is, the polyimide compositions of Examples 4 to 12, are polyimide resins capable of forming cured films having a low dielectric constant, a low dielectric tangent, a high elastic modulus, and a low coefficient of linear thermal expansion, while providing coating films with a fast re-dissolving rate. In addition, in the polyimide composition of the present invention, polyimide compositions 5 to 12 of embodiment A, which further contain an epoxy compound having three or more epoxy groups in one molecule and having a glycidylamine moiety, have been shown to have improved adhesion to inorganic compounds (SiN) and metals (Cu). Moreover, it was shown that when a silane coupling agent was further contained in the polyimide composition of embodiment A, as in the case of polyimide compositions 8 to 12, the adhesion to metal (Cu) was improved.

Claims

1. A polyimide resin comprising structural units represented by the following formula (1) in an amount of 40 mol % or more and less than 70 mol % of all structural units, and structural units represented by the following formula (2) in an amount of more than 10 mol % and not more than 60 mol % of all structural units. 【Chemistry 1】

2. 2. The polyimide resin according to claim 1, which has a weight average molecular weight of 150,000 or more as calculated on a polystyrene basis by gel permeation chromatography.

3. 3. The polyimide resin according to claim 1, further comprising a structural unit represented by the following formula (3) in an amount of 20 mol % or less based on all structural units: 【Chemistry 2】

4. A polyimide composition comprising the polyimide resin according to any one of claims 1 to 3 and an organic solvent.

5. 5. The polyimide composition according to claim 4, further comprising an epoxy compound having three or more epoxy groups in one molecule and having a glycidyl amine moiety.

6. The polyimide composition according to claim 5 , further comprising a compound represented by the following general formula (A): 【Chemistry 3】 (In formula (A), R a represents a monovalent group containing at least one selected from the group consisting of a glycidyl group, a (meth)acryloyl group, an acid anhydride group, a hydroxyl group, a triazine group, and an amino group; R b and R c are each independently an alkyl group having 1 to 5 carbon atoms, n is an integer of 1 to 10, and m is an integer of 1 to 3.

7. A step of applying the polyimide composition according to any one of claims 4 to 6 onto a substrate and drying the composition to form a coating film; The method for producing a cured film of a polyimide composition includes a step of heating the coating film to form a cured film.

8. The method for producing a cured film of a polyimide composition according to claim 7, wherein the temperature at which the coating film is heated is 150°C or higher and 240°C or lower.

9. A cured film of the polyimide composition obtained by curing the polyimide composition according to any one of claims 4 to 6.

10. 10. A cured film of the polyimide composition according to claim 9, having a dielectric constant of 3.60 or less and a dielectric dissipation factor of 0.020 or less, as measured at 10 GHz using a split cylinder resonator.

11. 11. A cured film of the polyimide composition according to claim 9 or 10, having a linear thermal expansion coefficient of 30 ppm / °C or less at 100°C to 150°C.

12. The cured film of the polyimide composition according to any one of claims 9 to 11, having a tensile modulus at 25°C of 4.5 GPa or more.

13. 7. A cured film of the polyimide composition obtained by curing the polyimide composition according to claim 5 or 6, wherein the adhesion to a silicon nitride substrate is such that the number of unpeeled cross-cuts in a cross-cut test according to JIS K 5400-8.5 is 80% or more of the total.

14. An insulating film produced using a cured film of the polyimide composition according to any one of claims 9 to 13.

15. A protective film produced using a cured film of the polyimide composition according to any one of claims 9 to 13.

16. An electronic component comprising the insulating film of claim 14 or the protective film of claim 15.

Citation Information

Patent Citations

  • Sensor for combustion safety device

    JP1986065153A

  • Soluble polyimide

    JP1988046225A

  • Rear seat back for automobile

    JP1989067433A

  • Multi-chip module circuit board

    JP1995106724A

  • Polyimide resin composition for semiconductor apparatus, method for forming film in semiconductor apparatus and semiconductor apparatus

    JP2011178855A